Anisotropic Self‐Assembly of Citrate‐Coated Gold Nanoparticles on Fluidic Liposomes. (23rd February 2016) - Sugikawa, Kouta; Kadota, Tatsuya; Yasuhara, Kazuma; Ikeda, Atsushi
Abstract: The behavior of self‐assembly processes of nanoscale particles on plasma membranes can reveal mechanisms of important biofunctions and/or intractable diseases. Self‐assembly of citrate‐coated gold nanoparticles (cAuNPs) on liposomes was investigated. The adsorbed cAuNPs were initially fixed on the liposome surfaces and did not self‐assemble below the phospholipid phase transition temperature ( T m ). In contrast, anisotropic cAuNP self‐assembly was observed upon heating of the composite above the T m, where the phospholipids became fluid. The number of self‐assembled NPs is conveniently controlled by the initial mixing ratio of cAuNPs and liposomes. Gold nanoparticle protecting agents strongly affected the self‐assembly process on the fluidic membrane.